Agility assessment through qualification and quantification tools: a case study in an Indian pump manufacturing company. (20th March 2007) - Ramesh, G.; Devadasan, S.R.
The Indian pump manufacturing industry, which has provided large volumes of jobs to the engineering community and contributed significantly to the Indian economy, is currently facing downward trend in a competitive scenario. This is due to the fact that a major portion of the Indian pump manufacturing industry is yet to become agile. There are similar industrial sectors located in different parts of the world that experience the same trend in the global market and are yet to become agile. However, those industrial sectors need guidance to assess their levels and determine the actions to be carried out for progressing towards agility. In order to meet this requirement, this article is being brought out with the tools for qualifying and quantifying agility in manufacturing companies. A case study has been reported, which will guide the captains of industries to these tools.